Enhancement potency of math club activities on junior secondary school students' mathematics learning (2013)
Mathematics has been described as a precision tool used by all scientists in their search for clear understanding of the physical world. It plays a pivotal role in enabling science and technology contribution to national development. To be precise, it several and varied applications in all fields of human endeavours can never be over emphasised. Considering the importance of the causes of this is the way and manner in which the subject is being presented to the students. This is the more reason why a study of this nature is being carried out to see how a social based strategy (math club activities) can be used to enhance students' attitude towards and achievement in mathematics. The study adopted quasi-experimental design and used purposive sampling method to select four (4) public schools for the study (2 experimental and 2 control groups). Intact classes were used as control groups while only members of math club formed the participants in the experimental group. In all, 204(104 male, 100 female) J. S 2 students were used for the study. Four (4) research instruments were used for the study, Mathematics Achievement Test(MAT), Student Mathematical Attitude Scale (SMAS). General Intelligence Test (GIT) and Treatment Package(TP). The treatment lasted for four weeks and the data collected was subjectd to Analysis of Covariance (ANCOVA) using SPSS software. The result of study shows that there was a significant main effect of treatment (Math Club Activities) on students' achievement in mathematics F(1.195)=35.614,p<.05 and attitude towards mathematics F=1.195)=15.457,p<0.5. However, the effect of gender on students' achievement and attitude towards mathematics was not statistically significant. Based on the result of the findings, it was revealed that involvement of students in math club activities has greatly influencedn students' achievement in and attitude towards mathematics. Therefore stakeholders in mathematics education should exploit the maximum benefits embedded in math club to improve achievement in and attitude of students towards mathematics.